The Reconfiguration of Contemporary Islamic Sufism: Global Scholarly Trends and Their Relevance to Sufi Da'wah in Indonesia - Muhammad Choirin; Ahmad A'to'a Bin Mokhtar; Fakhrul Adabi Bin Abdul Kadir (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
Contemporary Islamic Sufism is experiencing dynamic structural adjustments as academic scrutiny increases regarding its capacity to address modern spiritual and socio-ethical dilemmas. Despite extensive literature, a comprehensive mapping of global scholarly trajectories and their analytical translation into localized Islamic propagation (da'wah) models remains critically absent. This study examines global research trends in contemporary Islamic Sufism, identifying its intellectual architecture, thematic evolutions, and strategic relevance to Sufi-oriented da'wah in Indonesia. Utilizing a hybrid bibliometric approach integrated with qualitative content analysis, this study evaluates 96 Scopus-indexed publications spanning 2015–2024. Unless otherwise specified, references to “global” scholarship throughout this study denote this Scopus-indexed, English-language corpus rather than the full body of worldwide Sufism literature. Bibliometric indicators, including co-citation networks and thematic mapping, were analyzed via the Biblioshiny package in R. The findings reveal a significant paradigm shift in contemporary Sufi scholarship, moving from isolated esoteric-mystical dimensions toward an active, highly interdisciplinary discourse. The intellectual structure has reconfigured around themes of religious moderation, ethical spirituality, social resilience, and public engagement. This study offers a preliminary conceptual contribution by bridging bibliometric insights with localized practices, proposing a tentative framework for "engaged Sufism"—built on the recurring thematic clusters of religious moderation, ethical spirituality, social resilience, and public engagement identified in the bibliometric mapping. This framework provides an inclusive, contextual, and transformative foundation for contemporary da'wah models within Indonesia’s pluralistic society.